2018
DOI: 10.1002/asia.201800532
|View full text |Cite
|
Sign up to set email alerts
|

Sulfur‐Center‐Involved Photocatalyzed Reactions

Abstract: Sulfur-containing compounds (SCCs) exist widely in, for example, natural sources, pharmaceuticals, materials, and foods. Their multifarious functions have stimulated scientists to construct them in greener and more efficient ways and further exploit their properties. Different photosensitizers with sulfur atoms have been developed and exploited. Furthermore, SCCs display excellent ability in hydrogen-atom-transfer reactions. In addition to acting as catalysts, SCCs can also be efficiently transformed under vis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 58 publications
(15 citation statements)
references
References 133 publications
(174 reference statements)
0
15
0
Order By: Relevance
“…Based on our longstanding interest in sulfur chemistry, we commenced our investigation by irradiating p ‐tolyl butyl sulfide ( 1 a ) with blue LEDs under an oxygen atmosphere in the presence of uranyl acetate as the catalyst. A solvent screen (Table S1, entries 1–4) showed that acetonitrile was beneficial for the generation of sulfone 3 a (43 %).…”
Section: Resultsmentioning
confidence: 74%
“…Based on our longstanding interest in sulfur chemistry, we commenced our investigation by irradiating p ‐tolyl butyl sulfide ( 1 a ) with blue LEDs under an oxygen atmosphere in the presence of uranyl acetate as the catalyst. A solvent screen (Table S1, entries 1–4) showed that acetonitrile was beneficial for the generation of sulfone 3 a (43 %).…”
Section: Resultsmentioning
confidence: 74%
“…The intermediates 6-substituted-3-mercapto-1,2,4-triazin-5-ones 1a-1e were prepared using known methods [15,21]. Sulfur atoms have a larger size and lower electronegativity than those of oxygen atoms, which makes the outer electron shell more prone to donate electrons, and results in most likely nucleophilic attack [22]. The intermediates 1a-1e underwent selectively rapid S-alkylation reaction, in which any possible N-, O-, or C-alkylation of the same substrate is much slower and hence negligible [23,24].…”
Section: Chemistrymentioning
confidence: 99%
“…Sulfur‐containing compounds serve important functions in organic synthesis, such as substrates, photosensitizers or hydrogen‐atom‐transfer (HAT) reagents and so on Thioethers as important building blocks in some important drugs or some biologically active compounds (shown in Figure ) have led to an increased awareness of researchers . At present, a variety of methods for the corresponding synthesis of thioethers are available in the literatures .…”
Section: Introductionmentioning
confidence: 99%